Review of Pastoralists’ Resilience and Adaptation to Climate Change: Can Technology Help Pastoralists Mitigate The Risks? - Arjjumend, Hasrat (International Journal of Bio-resource and Stress Management, 2018)
In the changing environments globally, it is essential to look deeply into the effects of climate change on rangelands, pastoralists and livestock grazing, and into how the pastoralists cope with the climatic changes and challenges. There is a scientific rationale behind the pastoralists’ adaptation strategies for coping with the climate variability. The present review-based paper explores how the rangelands and nomadic pastoralism are critical for grassland biomes and ecosystems. It is scientifically es tablished that the pastoralist lifestyles are not only most sustainable in present times but also most resilient, given the challenges of climatic variability. As the changing climates globally pose threats to grassland ecosystems and associated natural resources, pastoralists and their livestock are affected greatly by erratic weathers and changing availability of palatable biomass. Available literature proves that the pastoralist people hold much of the knowledge about how to adapt in hostile and varying climates. For example, the pastoralists adopt strategies such as rotational use of pasturelands, division of livestock, diversification of livestock, predicting rainfall and seasonal changes, and so on. In addition to understanding the resilience and adaptation strategies of pastoralists, present paper addresses how the technology might help nomadic pastoralists build their resilience on the face of climate change. This paper finally discusses the need to test various technologies in biological, ecological and anthropological contexts of the rangelands and pastoralism so that dying lifestyles and cultures of the marginalized nomadic people can survive in hostile climate change regime.